Foundations of expressive arts therapy : theoretical and clinical perspectives - Levine, Stephen K.; Levine, Ellen G. (J. Kingsley Publishers, 1999)
Foundations of Expressive Arts Therapy provides an arts-based approach to the theory and practice of expressive arts therapy. The book explores the various expressive arts therapy modalities both individually and in relationship to each other. The contributors emphasize the importance of the imagination and of aesthetic experience, arguing that these are central to psychological well-being, and challenging accepted views which place primary emphasis on the cognitive and emotional dimensions of mental health and development. Part One explores the theory which informs the practice of expressive arts therapy. Part Two relates this theory to the therapeutic application of the expressive arts (including music, art, movement, drama, poetry and voicework) in different contexts, ranging from play therapy with children to trauma work with Bosnian refugees and second-generation Holocaust survivors. Comprehensive in its coverage of the most fundamental aspects of expressive arts therapy, this book is a significant contribution to the field and a useful reference for all practitioners.